Implementasi Reward Asyik dalam Meningkatkan Rasa Percaya Diri Anak Kelompok B TKIT Almarjan Bekasi - Alis Hamidah; Anis Diah Utami; Iting Sugiarti; Ummul Faizah Rohmatin; Rofiati Rofiati; Sri Watini (Syntax Corporation Indonesia, 2024)
Early Childhood Education is an effort to provide stimulus for children from birth to six years of age. Education during the golden age is carried out to help children's growth and development, both physically and spiritually, so that children are ready to enter further education. One aspect of development is social emotional development, including self-confidence. This research aims to increase the self-confidence of children aged 5-6 years through